TEMPORAL AND SPATIAL VARIATIONS OF AMBIENT DOSE EQUIVALENT RATE IN URBAN AND RURAL SITES - Gulan, Ljiljana (Bulletin of Natural Sciences Research, 2018)
This study deals with the results of measuring the ambient dose equivalent rates conducted in test field. The impacts of temporal and weather variations (wind, precipitation, moisture, temperature) as well as spatial characteristics (rural and urban sites) on the ambient dose equivalent rate were analyzed. Mean ambient dose equivalent rate in rural site (142 nSv/h) is higher than in urban site (128 nSv/h). The reason is difference in altitude and also the difference in the local geology. Although an increasing of temperature, decreasing the moisture in air, and slowing down the wind speed during the observed period showed tendency of stability the ambient dose equivalent rate, no correlation was found between ambient dose equivalent rate and any parameter.